EKSISTENSI MAHAR DALAM PERKAWINAN MENURUT KHI DAN FIQH ISLAM - Faisal Faisal (STISNU Aceh, 2022)
This research talks about the existence of dowry, which in fact found that the practice of dowry is a very urgent thing in the life of Muslims. Likewise, the existence of dowry in fact is also very important in a marriage. This research is classified as literature research with a qualitative approach. The methodology in this article uses the legal research method. This research tries to reveal the existence of dowry in a marriage according to legal opinions, namely the views of the Compilation of Islamic Law (KHI) and Islamic fiqh, of course this study will try to elaborate on the concepts contained in marriage regulations in Indonesia or KHI with Islamic fiqh.